Prosedur Aktualisasi Manajemen Risiko Pendidikan dalam Meningkatkan Kualitas Pendididikan - Setiawan, Farid; Ningsih, Ambar Wati; Nurgiansyah, Herpin; Rohman, Ilham Abdur (TSAQOFAH, 2022)
Risk is something that can occur when an organization's activities are carried out. The risks that occur can be in the form of opportunities or challenges so that in their management there is a need for planning. Educational risk management as planning in carrying out activities in an institution, especially school education. Good planning will improve the quality of an education. The discussion in this article is about how the education management process can improve the quality of education. Writing articles using a literature study approach. The result of writing is that risk management in education needs to be done as an effort to improve and develop the quality of education.